2021
DOI: 10.3390/children8110979
|View full text |Cite
|
Sign up to set email alerts
|

Positive Airway Pressure Therapy for Pediatric Obstructive Sleep Apnea

Abstract: Pediatric obstructive sleep apnea syndrome (OSAS) is a disorder of breathing during sleep, characterized by intermittent or prolonged upper airway obstruction that can disrupt normal ventilation and/or sleep patterns. It can affect an estimated 2–4% of children worldwide. Untreated OSAS can have far reaching consequences on a child’s health, including low mood and concentration as well as metabolic derangements and pulmonary vascular disease. Most children are treated with surgical intervention (e.g., first-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 63 publications
(86 reference statements)
0
8
0
Order By: Relevance
“…Additionally, there are auto-adjusting CPAP/BPAP devices that utilize a unique algorithm. These devices might be useful when the severity of OSA is dependent on body posture and/or sleep stage [56]. CPAP titration with an auto-CPAP device in the home environment can be considered for children when access to a sleep laboratory is limited [57].…”
Section: Positive Airway Pressurementioning
confidence: 99%
“…Additionally, there are auto-adjusting CPAP/BPAP devices that utilize a unique algorithm. These devices might be useful when the severity of OSA is dependent on body posture and/or sleep stage [56]. CPAP titration with an auto-CPAP device in the home environment can be considered for children when access to a sleep laboratory is limited [57].…”
Section: Positive Airway Pressurementioning
confidence: 99%
“…A variety of training techniques that include positive reinforcement, gradual exposure to the use of PAP and the use of the equipment in association with pleasurable activities for the child are described in the literature. The current literature does not suggest that any specific desensitization strategy is superior to any other 279 . Regardless of the method, desensitization strategies should be playful in nature.…”
Section: Sleep Breathing Disorders In Pediatricsmentioning
confidence: 74%
“…Desensitization strategies that help the child to gradually become used to the treatment are indispensable. Strategies involving a multidisciplinary team have been shown to be more effective in increasing tolerance to the use of PAP 279 . A variety of training techniques that include positive reinforcement, gradual exposure to the use of PAP and the use of the equipment in association with pleasurable activities for the child are described in the literature.…”
Section: Sleep Breathing Disorders In Pediatricsmentioning
confidence: 99%
See 1 more Smart Citation
“…The predictors for post AT respiratory complications requiring intervention are children with severe OSA particularly AHI > 40/h, younger children (<2 years of age), lower oxygen saturation (SpO 2 ), and poor nutritional status which was shown in a retrospective review conducted by Saeid et al [ 14 ]. For children where surgery is not indicated or desired, or for those with postoperative residual OSAS, positive airway pressure (PAP) therapy can be an effective treatment [ 15 ]. Benke et al study showed that the use of autoCPAP is effective and safe for the treatment of OSAS in pediatric patients with obesity [ 16 ].…”
mentioning
confidence: 99%